KESADARAN HUKUM PENCATATAN PERKAWINAN PENGHAYAT KEPERCAYAAN SAPTA DARMA DI KOTA MALANG - Jovita Dwi Caroline Halan; Fitri Hidayat; Rumi Suwardiyati (Law Department Jenderal Achmad Yani University, 2025)
Sapta Darma belief adherent couples in Malang City are legally obligated to register their marriages with the Department of Population and Civil Registration (Dispendukcapil), in accordance with Law Number 24 of 2013 concerning Population Administration. Although adherents of local religions have been legally recognized, in practice, many couples have yet to officially register their marriages. This research aims to analyze the level of legal awareness among Sapta Darma adherents regarding marriage registration in Malang City. This research is a type of socio legal research that uses sociological jurisprudence approach. Primary data were obtained through interviews with informants, while secondary data were gathered from law and official document. The population in this research is Sapta Darma adherent couples as well as leaders and elders of the Sapta Darma Citizens Association (Persada) in Malang City. The sample in this research uses non-probability sampling using the quota sampling method and that are analyzed using qualitative descriptive analysis. Based on the results of the research, the legal awareness of Sapta Darma belief-based couples in Malang City is not yet optimal, or can even be categorized as lacking legal awareness. Although most couples possess basic knowledge about the obligation to register their marriages, their legal attitudes do not fully comply with the applicable legal provisions. The state has, in fact, provided a clear legal foundation to guarantee the rights of believers. However, the existence of such legal regulations is not sufficient to ensure their effective implementation.